Effect of Addition of Seaweed (Sargassum Sp) Charcoal with Pure Graphite on The Optical Properties of Graphene Oxide Synthesized by the Modified Hummer’S Method - kurniawati, Rega; Ramli, -; Gusnedi, -; Hidayat, Rahmat (Department of Physics – Universitas Negeri Padang UNP, 2024)
Synthesis of graphene oxide from a mixture of pure Graphite and seaweed charcoal using a modified Hummers method was carried out with five variations of the composition, namely 100% graphite, 70% graphite– 30% seaweed, 60% graphite – 40% seaweed, 50% - 50%, 100% seaweed. From this experiment, it will be seen how adding seaweed with Graphite affects the optical properties of the resulting graphene oxide. Characterization was carried out using FTIR, XRD, and SEM, and for optical properties, a UV-Vis Spectrophotometer was used. The FTIR test results showed the presence of carbon (C), hydrogen (H), and oxygen (O) functional groups. The XRD test results showed the crystal size of graphene oxide, and the SEM test showed graphene oxide's morphology in the form of thin sheets and chunks. The FTIR, XRD, and SEM tests showed that adding seaweed with Graphite had no effect. The results of the UV-Vis Spectrophotometer test showed that the highest absorbance value was at a variation of 50% - 50%, namely 49.547 at a wavelength of 245 nm, while for the lowest energy gap value, namely the variation of 100% seaweed 2.2875 eV and the highest 100% graphite 4, 2393 eV, the energy gap shows that there is an influence, the more seaweed composition used, the lower the energy gap